ANALISIS TREND PRODUKSI KELAPA SAWIT DI PT PERKEBUNAN MINANGA OGAN KECAMATAN LUBUK BATANG KABUPATEN OKU (JASEP, 2018)
Analysis Of The predicts oil palm prodution The Village Of Source PT Perkebunan Minanga Ogan Kecamatan Lubuk Batang Of Oku. This research aims to analyze the trend of production of oil palm plantation pt minanga ogan coming five years that was implemented in February 2017. This research was carried out at pt plantation minanga ogan. The research method used is the method of the study of the literature, namely, the methods used for this type of research using secondary data (examines the results of existing studies). The data collected in this research in the form of time series data of annual secondary data from the year 2011 to 2017. The results showed that the analysis of the trend of production of palm plantation pt sawut minanga ogan five years predicted by the method and the processing and analysis of data and using the method of least square (the smallest squares method) shows the results of. 12.02005 kg/bln. The production of palm oil increased each month